Dyslipidemia patterns and associated factors in Wilson’s disease patients: a clinical analysis - Wu, Rong; Luo, Xingguang; Wang, Xiao-Ping (Frontiers in Neurology, 2024)
ObjectiveThis study aims to analyze the lipid metabolism patterns and identify risk factors for dyslipidemia in Wilson’s Disease (WD), offering novel insights into diagnosis and treatment strategies for unexplained dyslipidemia.MethodsData from Wilson’s disease patients hospitalized at the First People’s Hospital of Shanghai from December 2008 to February 2015 were collected. Patients were categorized into normal lipid (46 cases) and dyslipidemia (42 cases) groups based on lipid levels. Group analyzes were conducted using t-tests, chi-square analysis, and rank sum tests. Spearman correlation, multiple linear regression, or Logistic regression were employed to identify relevant influencing factors.Results1. The incidence of abnormal blood lipids in a series of Wilson’s disease patients was 47.73% (25.12 ± 1.29 years old), and the incidence of control healthy group was 27.40%, with proportions of hypercholesterolemia, hypertriglyceridemia, and low-density lipoprotein cholesterol being 14.77, 30.68, and 29.63%, respectively; 2. Significant differences were observed between the dyslipidemia and normal WD groups in AST/ALT ratio, liver parenchymal echo, liver surface, spleen area, and ultrasound total score.3. Low-and high-density lipoprotein cholesterols (LDL-c and HDL-c) showed no significant correlation with these indicators. Triglyceride (TG) exhibited moderately negative correlation with AST/ALT, liver parenchymal echo, spleen area, and ultrasound score. Total cholesterol (TC) displayed low negative correlation with these factors.Conclusion1. Dyslipidemia incidence in Wilson’s disease patients may exceed that of the normal population, especially in adolescents with unexplained abnormal lipid metabolism; 2. Patients with mild to moderate liver damage are predisposed to elevated triglycerides and total cholesterol, reflecting liver damage impact on lipid metabolism; 3. Glucose metabolism is not implicated in WD-related dyslipidemia; 4. No significant correlation was found between abnormal lipid metabolism and blood concentration of trace elements in WD patients.